Psychometric properties of physical activity questionnaires for children and adolescents: an updated systematic review - Rostami Haji Abadi, M.; Kwaghbo, N.; Onyeso, O. K.; Sadia, F.; Benavides Castro, J. K.; Santos Silva, D. A.; Yan, Y.; Shen, Y.; Hamrik, Z.; Sarmiento, O. L.; Liu, Y.; Tremblay, M. S.; et al. (Sports Medicine, 2025)
Background: Questionnaires remain the most feasible method for large-scale physical activity (PA) surveillance. However, previous systematic reviews concluded that existing questionnaires had unsatisfactory psychometric properties. Objectives: This systematic review aimed to summarize and evaluate the measurement properties of self- and proxy-reported physical activity (PA) measures in children and adolescents published between 2018 and July 2024, thereby updating a previous review. This review also aimed to recommend the best available questionnaire(s) for young children (age < 6 years), children (age = 6 to < 12 years), and adolescents (age = 12 to < 18 years). Methods: The COnsensus-based Standards for the Selection of Health Measurement INstruments (COSMIN) Guidelines for Systematic Reviews of Patient-Reported Outcome Measures were followed for conducting and reporting this systematic review. PubMed, EMBASE, and SPORTDiscus databases were searched for papers published between 2018 and July 2024. The peer-reviewed papers were included if published in Arabic, Chinese, Czech, English, French, Hindi, Nepali, Portuguese, Spanish, Swedish or Thai and assessed at least one of the measurement properties of self- or proxy-reported PA measures in young children, children, and adolescents. Papers were excluded if they measured PA with interview or diary or reported construct validity against non-PA measures (e.g., body mass index). The results of studies from the previous systematic review that reported test-retest reliability and construct validity of the questionnaires included in this systematic review were added to the pooled qualitative analyses and meta-analyses. Results: A total of 106 papers were included which reported 177 studies related to content validity (n = 31), construct validity including hypotheses testing (n = 80), test-retest reliability (n = 65), and responsiveness (n = 1) of 71 questionnaires. None of the included questionnaires met the COSMIN criteria for sufficient content validity. Questionnaires with satisfactory construct validity (correlation r = 0.4) were found in young children (n = 2; e.g., the Outdoor Playtime Recall), children (n = 2; e.g., Self-rating Scale of Physical Activity Intensity for Preschool Children), and adolescents (n = 8; e.g., the Spanish version of Physical Activity Unit 7 Item Screener, the Czech version of Youth Activity Profile). Questionnaires with sufficient test-retest reliability (= 0.7) were found in young children (n = 2; e.g., the Movement Behaviour Questionnaire for Baby and Children), children (n = 3; e.g., Diet and Physical Activity Behaviors in the Feel4Diabetes Study), and adolescents (n = 5; e.g., the 24-Hour Movement Behavior Questionnaire). The Physical Activity Questionnaire for older Children and Adolescents had sufficient test-retest reliability based on pooled qualitative analysis and meta-analyses. The best available questionnaires were the Outdoor Playtime Recall (for young children) and the Physical Activity Questionnaire for Older Children and Adolescents for children and adolescents. Conclusion: This systematic review update did not identify a PA questionnaire that met COSMIN standards for both construct validity and test-retest reliability, partly due to the low methodological quality of the studies. Researchers should improve the methodological rigor of future psychometric studies, particularly for content validity, by adopting standardized guidelines (e.g., COSMIN). We also recommend: (1) using comparator tools that have demonstrated reliable measurement properties in populations similar to the target group; (2) formulating hypotheses in advance to confirm construct validity; (3) selecting appropriate intervals between test and retest and ensuring consistent test conditions; and (4) providing evidence of PA stability between test and retest. Lastly, when developing questionnaires to measure total PA, researchers should include all relevant domains of PA and assess their relevance during the content validation process.